Role of C-type Lectin Receptor to C.albicans on Promotion of Inflamantory Diseases - Erna Sulistyani (Denta Journal Kedokteran Gigi, 2017)
In early 2010 there was a very rapid progress in the development of immunity to fungi, i.e the discovery of CLR. CLR is one of the PRR receptors found in immune cells that recognize the cell wall of fungi and then trigger a transduction signal that eventually provoke the production of various proinflamatory include IL1β, IL6, TNF α and induce polarization Th17. In the condition of infection the number of innate immune cells increases dramatically, lead to increasing of cytokines produced. Both cytokines and the cells that produce them enter the bloodstream. If there is unbalance level of pro and anti inflammatory cytokine, various inflammatory and/or autoimmune diseases can be occur. Unlike the focal concept infection, where the agent will cause disease if enters the blood vessels, through this concept a fungal infection at epithelium can lead to inflammatory diseases in other part of body without having to go through fungus